Perfil de saúde laboral e auditiva de trabalhadoras e as ações afirmativas em indústrias do Paraná - Rocha, Marcia Fernanda Vieira (2015)
Introduction: Over time, the culture was assigning different roles to men and women that impact the health of each sex. Culturally men's mission is to quell emotions, the exercise of power, maintain control, denial of behavior in favor of masculinity and other aspects leading to serious health consequences. But the role assigned to women is the care for others how to raise children, meet the family, housework and so society has created mechanisms of domination and discrimination that breeds fear, dependency and negatively impacts health. Objective: To analyze the profile of occupational health and hearing of workers in three industries of different segments of Paraná. Methodology: This study is a quantitative, transversal approach. 150 workers in 3 Paraná industries were interviewed. Frequencies and percentages for each variable were calculated for each of the industries and for all the same. Comparative analyzes were performed taking into account the segment that every company. For association analysis between variables we used the chi-square test at the 0.05 significance level. Results: The age distribution in the three industries was 25-34 years. Regarding education, the largest number of workers had high school. The marital status of most workers was married, or held consensual union. Regarding the number of children, the predominant group was the 1-2 children. Of respondents, 73% had activities in the production area and 58% did some professional courses. The monthly income of women was in the range of R $ 700.00 to R $ 1,499.00, and family income, ranging from R $ 1,500.00 to R $ 2,500.00, 42% were the breadwinners. 17% of working acquired disease at work and 9% suffered accident trabalho.86% say that industries request periodic examinations, and the frequency of examinations that were more appear in semi-annual / annual range. Regarding the participation of workers in events and / or health campaigns promoted by industries, it was noted that a greater number of participating 63%. Most workers (75%) have the perception of risks in the workplace, and the noise was the most identified risk, the three participants of the survey industries, followed by the falls and the ergonomics issues through repetitive motion. The three industries hold regular hearing tests, as reported the trabalhadoras.As workers considered noisy work environment, especially those in the construction industry segment, followed by the metallurgical industry. And are these same industries where most women claimed to use PPE, 100% and 82%, respectively. Conclusions: It became relevant to discussion of the importance of women workers in the world today. However, the challenge to identify certain priorities, the economic environment, socio-demographic and epidemiological current is still great. In this study it was found that workers perceive the risks in the workplace, use personal protective equipment and collective and perform periodic medical examinations. There is no relationship between education and self-perception of health, health problems and diseases at work but there is a relationship between education and the demand for care workers médica.As participation of educational health actions promoted by industries that use events allusive dates to address issues related to women's health.